Línea sur 5 : foreign policy journal, may / aug 2013 - Ministerio de Relaciones Exteriores y Movilidad Humana (Quito, Ecuador : Ministerio de Relaciones Exteriores y Movilidad Humana, 2013)
Línea Sur, the Foreign Policy Journal of the Ministry of Foreign Affairs and human mobility, receives submissions for publication continuously. Articules must conform to the publication guidelines of the journal and elaborate on themes related to the field of international relations, preferably as related to Ecuador.
Contenido Message from the minister of foreign affairs : Ricardo Patiño Aroca Dossier Presentation of the Dossier }The world system and its main characteristics The rights of nature, globalization, an climate change Strengthening the inter-american human rights system amendments to the inter-american commssion: brief reflections Profiting from injustice: How lasw firms, arbitratores, and financiers are fueling an investiment arbitration boom The perils of the investor state shystem Strategic agenda and integraction Andean trsnormativae neoconstituionalism and its connection to internacitonal human rights law The state, business, and human rights: challenges within the framework of good living Current affarirs After the april 14 elections: The political scene in Venezuela and the challenges of transition New united states battlefield technologies Interview The legitimate restructuring of the states role regarding transnational corportions in latin america: an interview with Pedro Ramiro Historial archives of the Ministry of foreging affarifs On cuenca's names Foreign Affarirs timeline
La Revista Línea Sur 5 se trabajó por analítica
incluye referencias bibliográficas en inglés
Incluye graficas
Keywords: POLÍTICA EXTERIOR -- AMÉRICA LATINA; ASUNTOS EXTERIOR -- AMÉRICA LATINA; LÍNEA SUR